2007
DOI: 10.1128/cvi.00094-07
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of a Combination of Two Serogroup B Meningococcal Outer Membrane Vesicle Vaccines

Abstract: MenBvac and MeNZB are safe and efficacious vaccines against serogroup B meningococcal disease. MenBvac is prepared from a B:15:P1.7,16 meningococcal strain (strain 44/76), and MeNZB is prepared from a B:4:P1.7-2,4 strain (strain NZ98/254). At 6-week intervals, healthy adults received three doses of MenBvac (25 g), MeNZB (25 g), or the MenBvac and MeNZB (doses of 12.5 g of each vaccine) vaccines combined, followed by a booster 1 year later. Two-thirds of the subjects who received a monovalent vaccine in the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 26 publications
(41 reference statements)
3
44
1
1
Order By: Relevance
“…Importantly, preclinical studies in mice have suggested that half the normal antigen dose of each OMV vaccine could elicit similar immune responses compared to full doses when administered in combination (16) and that sequential immunization with heterologous OMV strains could elicit broadly protective serum antibodies (17). The safety profile and immunogenicity of a combined OMV vaccine, consisting of MenBvac and MeNZB (half dose each) adsorbed to aluminum hydroxide, were then tested in a clinical trial design consisting of three primary doses given with 6-week intervals and a fourth booster-dose given 1 year later (18). With respect to antibody responses measured as serum bactericidal activity (SBA), opsonophagocytosis, and enzyme-linked immunosorbent assay (ELISA), the results showed that the immune responses to the combined vaccines were of the same magnitude as the homologous responses observed in control groups receiving individual vaccines (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, preclinical studies in mice have suggested that half the normal antigen dose of each OMV vaccine could elicit similar immune responses compared to full doses when administered in combination (16) and that sequential immunization with heterologous OMV strains could elicit broadly protective serum antibodies (17). The safety profile and immunogenicity of a combined OMV vaccine, consisting of MenBvac and MeNZB (half dose each) adsorbed to aluminum hydroxide, were then tested in a clinical trial design consisting of three primary doses given with 6-week intervals and a fourth booster-dose given 1 year later (18). With respect to antibody responses measured as serum bactericidal activity (SBA), opsonophagocytosis, and enzyme-linked immunosorbent assay (ELISA), the results showed that the immune responses to the combined vaccines were of the same magnitude as the homologous responses observed in control groups receiving individual vaccines (18).…”
mentioning
confidence: 99%
“…The safety profile and immunogenicity of a combined OMV vaccine, consisting of MenBvac and MeNZB (half dose each) adsorbed to aluminum hydroxide, were then tested in a clinical trial design consisting of three primary doses given with 6-week intervals and a fourth booster-dose given 1 year later (18). With respect to antibody responses measured as serum bactericidal activity (SBA), opsonophagocytosis, and enzyme-linked immunosorbent assay (ELISA), the results showed that the immune responses to the combined vaccines were of the same magnitude as the homologous responses observed in control groups receiving individual vaccines (18). In addition, the safety profile of the combined vaccine was not different from those previously seen after the administration of separate monovalent vaccines (1,6,9).…”
mentioning
confidence: 99%
“…In contrast to synthetic particulate systems, these OMV vaccines represent a unique system where the antigen and delivery vehicle together are derived from the Neisseria meningitidis pathogen itself (15,16). The proven safety and efficacy records of these OMV vaccines, particularly in The Netherlands (17) and in Norway (12,18), together with the knowledge that vesicles are produced by nearly all species of Gram-negative bacteria (including Escherichia coli), present the possibility of employing OMVs for the delivery of recombinant protein antigens. To date, however, antigens that are foreign to the parental bacteria remain notably absent from OMVs largely because of challenges associated with the transport of heterologous proteins to the vesicles (19).…”
mentioning
confidence: 99%
“…In contrast, SBA was strictly dependent on the presence of both C2 and high anti- on May 10, 2018 by guest http://iai.asm.org/ body levels. Consequently, it seems that complement-mediated opsonophagocytosis of meningococci can occur even in the presence of low background levels of antimeningococcal antibodies, while higher levels of antimeningococcal antibodies obtained by immunization are needed for detectable SBA to occur (37). The specificity of antimeningococcal antibodies probably also determines whether opsonphagocytosis or bactericidal effects will be effective (1).…”
Section: Discussionmentioning
confidence: 99%